Predicting nutritional composition of corn grain using near infrared reflectance spectroscopy - G. Garcia-Lagombra; L.H. Harbers (Kansas Agricultural Experiment Station Research Reports, 1991)
Corn grain samples collected over several years were used to develop equations for dry matter, crude protein, crude fiber, and ether extract (crude fat). Two computer models were used to select samples having a range of spectra (presumably a range of nutrient values) for developing calibration equations. Both methods selected an unexpectedly small number of samples; however, only the prediction of crude fiber appears questionable. Although coefficients of determination values are expected to be low with a small number of samples, standard errors of validation and prediction are consistently lower than those of standard (AOAC) methods, suggesting that the technology is reliable for nutrient analysis of corn grain.
Keywords: Cattlemen& #x27; s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Corn analysis; Near infrared spectroscopy